Erbium-ytterbium co-doped silica fiber and high-temperature induced phase separation anti-radiation treatment method thereof

The P2O5 phase separation structure is induced in the Erbium-ytterbium co-doped quartz fiber core through high-temperature gradient annealing process, which solves the problem of instability in the optical fiber in the radiation environment and improves the radiation resistance and gain characteristics of the optical fiber.

CN120328866APending Publication Date: 2025-07-18SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510491231.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing erbium-ytterbium co-doped quartz fibers have unstable performance in radiation environments, and have radiation damage and gain attenuation problems, making it difficult to operate stably in space laser communication systems for a long time.

Method used

The P2O5 phase separation structure is induced in the fiber core through a high-temperature gradient annealing process to form a nano-scale network, and the phospho-oxygen tetrahedron and silicon-oxygen network are used to construct a composite center to capture the defects generated by radiation and enhance the radiation resistance of the fiber.

Benefits of technology

It significantly reduces the gain attenuation of the fiber under 100 Krad X-ray radiation, extends the service life of the fiber, and maintains excellent optical performance and gain characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120328866A_ABST
    Figure CN120328866A_ABST
Patent Text Reader

Abstract

The invention discloses an erbium-ytterbium co-doped silica optical fiber anti-radiation treatment method based on high-temperature induced phase separation and an optical fiber product. According to the method, three-step high-temperature gradient annealing treatment is carried out on the erbium-ytterbium co-doped silica fiber containing P2O5 under specific conditions, a nanoscale P2O5 phase separation phenomenon is induced in a fiber core in an argon environment, and the stability and radiation resistance of the erbium-ytterbium co-doped silica fiber in a radiation environment are remarkably enhanced. Specifically, the annealing process effectively improves the microstructure characteristics of the fiber core glass, reduces the damage of radiation to the internal structure of the fiber core, and remarkably improves the radiation tolerance of the optical fiber. The erbium-ytterbium co-doped silica fiber prepared by the method is suitable for the fields with high radiation requirements such as space laser communication, laser radar, satellite remote sensing and the like, the service life of the erbium-ytterbium co-doped silica fiber in a space radiation environment can be remarkably prolonged, the fiber performance requirements in an extreme environment are met, and an efficient and controllable technical solution is provided for related applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to optical fiber technology and a method for optimizing its radiation resistance, and in particular to a method for improving the tolerance and stability of erbium-ytterbium co-doped quartz optical fiber in a radiation environment by high-temperature annealing. The invention belongs to the fields of optical fiber material engineering, radiation physics, and space application technology, and is particularly suitable for high-tech application scenarios such as space laser communication, laser radar, and satellite remote sensing that have extremely high requirements for optical fiber radiation resistance. Background Art

[0002] As a new type of high-speed communication technology, space laser communication has more significant advantages than traditional space microwave communication systems. It has shown excellent potential in terms of bandwidth capacity, system volume and weight, spectrum utilization, etc., especially in the context of not being restricted by the electromagnetic spectrum, it provides extremely broad application prospects in the fields of satellite communication, intersatellite communication and deep space exploration. The technological breakthroughs and multiple on-orbit verifications in this field in Europe, the United States, Japan and other countries have laid a solid foundation for the maturity of this technology. However, for my country, although certain progress has been made in the field of laser communication, the actual application of intersatellite laser communication is still in a critical transition stage from experimental verification to practical application. It faces bottlenecks in core technologies such as radiation-resistant erbium-ytterbium co-doped optical fiber, which need to be broken through to cope with the challenges brought by the space environment.

[0003] Erbium-ytterbium co-doped fiber is the core fiber material in space laser communication systems. It is widely used in key components such as fiber lasers and amplifiers. Its performance directly determines the power output and gain characteristics of fiber laser systems. The particularity of the space environment makes the application of erbium-ytterbium co-doped fiber face severe challenges. Especially under the influence of radiation damage, the performance and stability of fiber materials will be significantly affected. Under long-term exposure to space radiation, radiation damage may occur inside the optical fiber, resulting in increased optical loss and increased noise levels, which in turn affects the output efficiency and gain of the laser, and may even affect the stability and reliability of the entire communication system. Therefore, improving the radiation resistance of erbium-ytterbium co-doped fiber has become the key to ensuring the long-term stable operation of space laser communication systems.

[0004] In order to improve the radiation resistance of Er-Yb co-doped optical fibers, the mainstream technical solutions include doping with variable valence ions (such as Ce 3+ ,Ge 4 +etc.) and fiber optic carrier gas treatment (such as carrying H2, carrying D2, etc.). These methods have slowed down the radiation damage to a certain extent and delayed the decline of fiber optic performance. Variable valence ions have the property of electron transfer and can effectively inhibit the formation of color centers caused by radiation, thus slowing down fiber optic damage. However, excessive doping of variable valence ions may affect the gain and optical properties of the fiber optic, and under long-term high-energy radiation, its anti-radiation effect gradually weakens. Carrier gas treatment reduces color centers and fiber optic damage by reacting with radiation products, but faces problems such as gas leakage and long-term stability. Especially in extreme environments such as space, it is difficult to ensure gas tightness, resulting in the gradual failure of the protection effect. Although these two mainstream technical solutions have made certain progress in improving the radiation resistance of fiber optics, there are still certain limitations. Summary of the Invention

[0005] Aiming at the bottlenecks of low trapping efficiency and insufficient long-term stability in the existing anti-radiation technology of erbium-ytterbium co-doped silica fiber, the present invention proposes a technical solution based on the regulation of the glass micro-local structure: inducing the formation of a nano-scale phase separation structure with a size of <100 nm of P element in the core through a high-temperature gradient annealing process. This structure synergistically acts with the silicon-oxygen network through the phosphorus-oxygen tetrahedron [PO4] at the phase interface to construct a composite center with the ability to selectively capture vacancy defects, which can significantly extend the service life of the fiber optic in extreme radiation environments. Under X-ray radiation with a dose of 100 Krad, the gain attenuation coefficient of the erbium-ytterbium co-doped silica fiber treated by high-temperature-induced phase separation is reduced by more than 40% compared with the original sample.

[0006] The technical solution of the present invention is specifically an anti-radiation treatment method for erbium-ytterbium co-doped silica fiber based on high-temperature-induced phase separation, including the following steps: S1. Fabricate an optical fiber preform, the core composition of which contains 0.03 - 0.2 mol% Er2O3, 0.5 - 0.8 mol% Yb2O3, 5 - 15 mol% P2O5, 0 - 0.3 mol% CeO2, 0 - 1 mol% GeO2, and 0 - 3 mol% Al2O3, with the balance being SiO2, and then draw it into an erbium-ytterbium co-doped silica fiber through an optical fiber drawing tower; S2. Mechanically remove the coating from the erbium-ytterbium co-doped silica fiber obtained in step S1, and then ultrasonically clean the fiber surface with an ethanol-acetone mixed solvent; S3. Conduct high-temperature gradient annealing on the erbium-ytterbium co-doped silica fiber obtained in step S2 in an argon atmosphere to induce the formation of a P2O5 phase separation network structure in the core glass. The network structure consists of nanoparticles with a size of <100 nm and is distributed in a three-dimensional dispersion manner. The annealing process is divided into three stages: a) Heat up to 300 - 400 °C at a rate of 3 - 8 °C per minute and hold for 1 - 3 hours; b) Heat it up to 800 - 900 °C at a rate of 8 - 10 °C per minute and hold for 8 - 10 hours; c) Cool it to 300 - 500 °C at a rate of 10 - 20 °C per minute and then cool it in the furnace; S4. Use an ethanol - acetone mixed solvent to ultrasonically clean the surface of the erbium - ytterbium co - doped silica fiber obtained in step S3; S5. Conduct a secondary coating treatment on the erbium - ytterbium co - doped silica fiber obtained in step S4 to form an acrylic resin coating layer with a thickness of 50 - 80 μm on the fiber surface.

[0007] Furthermore, in step S1, a fiber preform is fabricated using plasma chemical vapor deposition (PCVD), modified chemical vapor deposition (MCVD), outside vapor deposition (OVD), or vapor - axial deposition (VAD).

[0008] Furthermore, in step S2, the blade edge angle of the peeling knife used in mechanical de - coating is 30 - 45°, the volume ratio of ethanol to acetone in the ethanol - acetone mixed solvent is 3:1 - 5:1, and the ultrasonic cleaning time is 20 - 30 minutes.

[0009] Furthermore, in step S3, the purity of argon is ≥99.999%, and the gas flow rate is 1.0 - 1.5 L per minute.

[0010] Preferably, in step S3, the three stages of the annealing process are specifically:  a) Heat it up to 350 °C at a rate of 5 °C per minute and hold for 2 hours;  b) Heat it up to 850 °C at a rate of 9 °C per minute and hold for 9 hours;  c) Cool it to 400 °C at a rate of 15 °C per minute and then cool it in the furnace.

[0011] Furthermore, in step S4, the volume ratio of ethanol to acetone in the ethanol - acetone mixed solvent is 3:1 - 5:1, and the ultrasonic cleaning time is 20 - 30 minutes.

[0012] Furthermore, in step S5, after the secondary coating treatment, heat - cure the fiber surface to ensure that the coating is firm and has good adhesion.

[0013] The technical solution of the present invention also includes an erbium - ytterbium co - doped silica fiber prepared by the above - mentioned preparation method. The core glass of the fiber has a P2O5 phase - separated network structure with a scale of <100 nm. Through the coordination of phosphorus - oxygen tetrahedra and silicon - oxygen networks at the phase interface, composite sites with the ability to capture vacancy defects are constructed. Under 100 Krad dose X - ray radiation, the gain attenuation coefficient of the silica fiber is reduced by more than 40% compared with the erbium - ytterbium co - doped silica fiber without high - temperature - induced phase separation treatment.

[0014] Advantageous technical effects of the present invention: By precisely regulating the microstructure of the core glass through a high-temperature annealing process, a P2O5 phase-separated network structure with a scale of <100 nm is induced to form. This structure constructs composite sites with the ability to capture vacancy defects through the coordination of phosphorus-oxygen tetrahedra and silicon-oxygen networks at the phase interface, and can selectively capture silicon atom vacancy defects and non-bridging hydroxyl color centers generated by radiation. Experiments show that under a 100 Krad dose of X-ray radiation, the gain attenuation coefficient of the erbium-ytterbium co-doped silica fiber treated by high-temperature-induced phase separation is reduced by more than 40% compared with the original sample. The damage caused by radiation to the fiber is significantly reduced, and excellent optical performance and gain characteristics are maintained. Description of the drawings

[0015] Figure 1 a is a microstructural diagram of the core glass inside the erbium-ytterbium co-doped fiber treated by high-temperature-induced phase separation in Example 1 under a high-resolution transmission electron microscope; Figure 1 b is a microstructural diagram of the core glass inside the erbium-ytterbium co-doped silica fiber without high-temperature-induced phase separation treatment in Comparative Example 1 under a high-resolution transmission electron microscope; Figure 1 c is the EDS line scanning path for the nanoscale phase-separated structure region in Example 1; Figure 1 d is Figure 1 the test result of the EDS line scanning path in c.

[0016] Figure 2 is a schematic diagram of the X-ray in-line radiation device.

[0017] Figure 3 is a graph showing the relationship between the change in gain and the cumulative total dose under in-line radiation for the erbium-ytterbium co-doped silica fiber treated by high-temperature-induced phase separation in Example 1 and the erbium-ytterbium co-doped silica fiber without high-temperature-induced phase separation treatment in Comparative Example 1.

[0018] Figure 4 is a graph showing the relationship between the change in gain and the cumulative total dose under in-line radiation for the erbium-ytterbium co-doped silica fiber treated by high-temperature-induced phase separation in Example 2 and the erbium-ytterbium co-doped silica fiber without high-temperature-induced phase separation treatment in Comparative Example 2. Detailed implementation manners

[0019] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to 3 embodiments and 2 comparative examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention: Example 1: S1. The fiber preform fabricated by MCVD is drawn at high temperature to obtain a 10 / 125 μm erbium-ytterbium co-doped silica fiber. The core composition of the fiber is: 0.05Er2O3 - 0.75Yb2O3 - 10P2O5 - 0.1Al2O3 - 89.1SiO2 (mol%); S2. A stripping knife with a blade angle of 45° is used to mechanically remove the coating from the erbium-ytterbium co-doped silica fiber. Subsequently, the fiber surface is ultrasonically cleaned with an ethanol-acetone mixed solvent with a volume ratio of 4:1 for 30 minutes; S3. Argon is used as the inert gas with a purity ≥99.999% and a gas flow rate of 1.5 L / minute. The cleaned silica fiber is subjected to high-temperature annealing treatment. The annealing process is divided into three stages:  a) Heat up to 350°C at a rate of 5°C / minute and hold for 2 hours;  b) Heat up to 850°C at a rate of 9°C / minute and hold for 9 hours;  c) Cool down to 400°C at a rate of 15°C / minute and then cool with the furnace; S4. The erbium-ytterbium co-doped silica fiber after high-temperature annealing treatment is ultrasonically cleaned with an ethanol-acetone mixed solvent with a volume ratio of 4:1 for 30 minutes; S5. The cleaned erbium-ytterbium co-doped silica fiber is subjected to secondary coating treatment to form an 80-μm-thick acrylic resin coating layer on the fiber surface to enhance its surface protection. After coating, appropriate heat curing treatment is carried out to ensure that the coating is firm and has good adhesion.

[0020] Figure 1 a is the internal microstructure diagram of the core glass of the erbium-ytterbium co-doped silica fiber after high-temperature induced phase separation treatment in Example 1 under a high-resolution transmission electron microscope. Figure 1 b is the internal microstructure diagram of the core glass of the erbium-ytterbium co-doped silica fiber without high-temperature induced phase separation treatment in Comparative Example 1 under a high-resolution transmission electron microscope. Comparison Figure 1 a and Figure 1 b show that obvious changes have occurred in the internal microstructure of the core glass of the erbium-ytterbium co-doped silica fiber after high-temperature induced phase separation treatment, that is, a P2O5 phase separation network structure with a scale of <100 nm has appeared inside the core glass of the erbium-ytterbium co-doped silica fiber induced by high-temperature annealing treatment. Figure 1 c is the EDS line scanning path for the nanoscale phase separation structure region in Example 1; Figure 1 d is Figure 1 the test result of the EDS line scanning path in c, confirming that the nanoscale phase separation structure is a phase separation network structure of P element..

[0021] Figure 2It is a schematic diagram of an X-ray on-line radiation device. All the optical fibers to be tested are tested under the same conditions to evaluate the change of the background loss of erbium-ytterbium co-doped silica fiber at 1080 nm with the dose under X-ray radiation. During the whole test process, only the erbium-ytterbium co-doped silica fiber to be tested is exposed to the radiation field, and the length of all the erbium-ytterbium co-doped silica fibers to be tested is 30 cm, and the signal optical power is 30 mW.

[0022] Figure 3 It is a graph showing the relationship between the gain change and the cumulative total dose of the erbium-ytterbium co-doped silica fiber after high-temperature annealing treatment in Example 1 and the erbium-ytterbium co-doped silica fiber without high-temperature annealing treatment in Comparative Example 1 under on-line radiation. It can be seen from the figure that after X-ray on-line radiation with a total dose of 100 krad, the gain attenuation of the erbium-ytterbium co-doped silica fiber after high-temperature annealing treatment in Example 1 is much lower than that of the erbium-ytterbium co-doped fiber without high-temperature annealing treatment in Comparative Example 1. It fully proves that high-temperature annealing can effectively improve the radiation resistance of erbium-ytterbium co-doped silica fiber.

[0023] Example 2: S1. Obtain an erbium-ytterbium co-doped silica fiber, and the core component of the fiber is: 0.05Er2O3-0.75Yb2O3-0.1Ce2O3-10P2O5-0.1Al2O3-89SiO2 (mol%); S2. Use a stripping knife with a blade angle of 30° to mechanically remove the coating of the erbium-ytterbium co-doped silica fiber, and then ultrasonically clean the fiber surface with an ethanol-acetone mixed solvent with a volume ratio of 5:1 for 20 minutes; S3. Use argon as the inert gas with a purity ≥99.999% and a gas flow rate of 1.2 L / minute to perform high-temperature annealing treatment on the cleaned silica fiber. The annealing process is divided into three stages:  a) Heat up to 300°C at a rate of 3°C / minute and hold for 1 hour;  b) Heat up to 800°C at a rate of 8°C / minute and hold for 8 hours;  c) Cool down to 300°C at a rate of 10°C / minute and then cool with the furnace; S4. Ultrasonically clean the erbium-ytterbium co-doped silica fiber after high-temperature annealing treatment with an ethanol-acetone mixed solvent with a volume ratio of 5:1 for 20 minutes; S5. Perform secondary coating treatment on the cleaned erbium-ytterbium co-doped silica fiber to form an 80-μm-thick acrylic resin coating layer on the fiber surface to enhance its surface protection. After coating, perform appropriate heat curing treatment to ensure that the coating is firm and has good adhesion.

[0024] Figure 4It is a graph showing the relationship between the change in gain and the cumulative total dose of erbium-ytterbium co-doped silica fiber treated by high-temperature induced phase separation in Example 2 and erbium-ytterbium co-doped silica fiber without high-temperature induced phase separation treatment in Comparative Example 2 under in-line radiation. As can be seen from the figure, under in-line X-ray radiation with a total dose of 100 krad, the gain attenuation of the erbium-ytterbium co-doped silica fiber treated by high-temperature induced phase separation in Example 2 is much lower than that of the erbium-ytterbium co-doped fiber without high-temperature induced phase separation treatment in Comparative Example 2. It is fully confirmed that the high-temperature induced phase separation treatment can effectively improve the radiation resistance of erbium-ytterbium co-doped silica fiber.

[0025] Example 3: S1. Obtain erbium-ytterbium co-doped silica fiber, and the core composition of the fiber is: 0.05Er2O3 - 0.75Yb2O3 - 0.1Ce2O3 - 1GeO2 - 10P2O5 - 0.1Al2O3 - 88SiO2 (mol%); S2. Use a stripping knife with a blade angle of 40° to mechanically strip the erbium-ytterbium co-doped silica fiber, and then ultrasonically clean the fiber surface with an ethanol-acetone mixed solvent with a volume ratio of 3:1 for 25 minutes; S3. Use argon as an inert gas with a purity ≥99.999% and a gas flow rate of 1.0 L / minute to perform high-temperature annealing treatment on the cleaned silica fiber. The annealing process is divided into three stages:  a) Heat up to 400°C at a rate of 8°C / minute and hold for 3 hours;  b) Heat up to 900°C at a rate of 10°C / minute and hold for 10 hours;  c) Cool to 500°C at a rate of 20°C / minute and then cool with the furnace; S4. Perform ultrasonic cleaning on the erbium-ytterbium co-doped silica fiber after high-temperature annealing treatment with an ethanol-acetone mixed solvent with a volume ratio of 3:1 for 25 minutes; S5. Perform secondary coating treatment on the cleaned erbium-ytterbium co-doped silica fiber to form an 80-μm-thick acrylic resin coating layer on the fiber surface to enhance its surface protection. After coating, perform appropriate heat curing treatment to ensure that the coating is firm and has good adhesion.

[0026] Comparative Example 1#: S1. Obtain erbium-ytterbium co-doped silica fiber, and the core composition of the fiber is: 0.05Er2O3 - 0.75Yb2O3 - 10P2O5 - 0.1Al2O3 - 89.1SiO2 (mol%), without high-temperature induced phase separation treatment.

[0027] Comparative Example 2: S1. Obtain an erbium-ytterbium co-doped silica fiber, the core composition of the fiber being: 0.05Er2O3 - 0.75Yb2O3 - 0.1Ce2O3 - 10P2O5 - 0.1Al2O3 - 89SiO2 (mol%), without undergoing high-temperature induced phase separation treatment.

Claims

1. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation, characterized in that, It includes the following steps: S1. Fabricate an optical fiber preform. The core composition of the optical fiber preform contains 0.03 - 0.2 mol% Er2O3, 0.5 - 0.8 mol% Yb2O3, 5 - 15 mol% P2O5, 0 - 0.3 mol% CeO2, 0 - 1 mol% GeO2, and 0 - 3 mol% Al2O3, with the balance being SiO2. Then, draw it into an erbium-ytterbium co-doped silica fiber through an optical fiber drawing tower; S2. Mechanically remove the coating from the erbium-ytterbium co-doped silica fiber obtained in step S1, and then ultrasonically clean the fiber surface using an ethanol-acetone mixed solvent; S3. Under an argon atmosphere, perform high-temperature gradient annealing on the erbium-ytterbium co-doped silica fiber obtained in step S2 to induce the core glass to form a P2O5 phase-separated network structure. The network structure consists of nanoparticles with a size of <100 nm and is distributed in a three-dimensional dispersion manner. The annealing process is divided into three stages: a) Heat it at a rate of 3 - 8 °C / min to 300 - 400 °C and hold for 1 - 3 hours; b) Heat it at a rate of 8 - 10 °C / min to 800 - 900 °C and hold for 8 - 10 hours; c) Cool it at a rate of 10 - 20 °C / min to 300 - 500 °C and then cool it in the furnace; S4. Ultrasonically clean the surface of the erbium-ytterbium co-doped silica fiber obtained in step S3 using an ethanol-acetone mixed solvent; S5. Perform a secondary coating treatment on the erbium-ytterbium co-doped silica fiber obtained in step S4 to form an acrylic resin coating layer with a thickness of 50 - 80 μm on the fiber surface.

2. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that In step S1, use plasma chemical vapor deposition (PCVD), modified chemical vapor deposition (MCVD), outside vapor deposition (OVD), or vapor axial deposition (VAD) to fabricate the optical fiber preform.

3. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that, In step S2, the cutting edge angle of the peeling knife used in the mechanical coating removal is 30 - 45°, the volume ratio of ethanol to acetone in the ethanol-acetone mixed solvent is 3:1 - 5:1, and the ultrasonic cleaning time is 20 - 30 minutes.

4. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that, In step S3, the purity of argon is ≥99.999%, and the gas flow rate is 1.0 - 1.5 L / min.

5. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 4, characterized in that In step S3, the annealing process is divided into three stages: a) Heat it at a rate of 5 °C / min to 350 °C and hold for 2 hours; b) Heat it at a rate of 9 °C / min to 850 °C and hold for 9 hours; c) Cool it at a rate of 15 °C / min to 400 °C and then cool it in the furnace.

6. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that, In step S4, the volume ratio of ethanol to acetone in the ethanol-acetone mixed solvent is 3:1 - 5:1, and the ultrasonic cleaning time is 20 - 30 minutes.

7. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that In step S5, after the secondary coating treatment, heat-cure the fiber surface again.

8. A method for radiation resistance treatment of erbium-ytterbium co-doped silica fiber based on high-temperature induced phase separation according to claim 1, characterized in that Under 100 Krad dose X-ray radiation, the gain attenuation coefficient of the erbium-ytterbium co-doped silica fiber is reduced by more than 40% compared with the erbium-ytterbium co-doped silica fiber without high-temperature-induced phase separation treatment.

9. An erbium-ytterbium co-doped silica fiber, characterized in that, Prepared by the method according to any one of claims 1-8, the core glass of the optical fiber has a P2O5 phase separation network structure with a scale of <100 nm. The structure constructs composite sites with the ability to capture vacancy defects through the coordination of phosphorus-oxygen tetrahedrons and silicon-oxygen networks at the phase interface. Under X-ray radiation with a dose of 100 Krad, the gain attenuation coefficient of the erbium-ytterbium co-doped silica optical fiber is reduced by more than 40% compared with the erbium-ytterbium co-doped silica optical fiber without high-temperature induced phase separation treatment.